CHAT gene polymorphism rs3810950 is associated with the risk of Alzheimer's disease in the Czech population - Hálová, Alice; Janoutová, Jana; Ewerlingová, Laura; Janout, Vladimír; Bonczek, Ondřej; Zeman, Tomáš; Gerguri, Tereza; Balcar, Vladimir J; Šerý, Omar (Journal of biomedical science (Basel. Online), 2018)
BACKGROUND: Cholinergic hypothesis of Alzheimer's disease (AD) is based on the findings that a reduced and/or perturbed cholinergic activity in the central nervous system correlates with cognitive decline in patients with Alzheimer's disease. The hypothesis resulted in the development of centrally-acting agents potentiating cholinergic neurotransmission; these drugs, however, only slowed down the cognitive decline and could not prevent it. Consequently, the perturbation of the central cholinergic signalling has been accepted as a part of the Alzheimer's aetiology but not necessarily the primary cause of the disease. In the present study we have focused on the rs3810950 polymorphism of ChAT (choline acetyltransferase) gene that has not been studied in Czech population before. METHODS: We carried out an association study to test for a relationship between the rs3810950 polymorphism and Alzheimer's disease in a group of 1186 persons; 759 patients with Alzheimer's disease and 427 control subjects. Furthermore, we performed molecular modelling of the terminal domain (1st-126th amino acid residue) of one of the ChAT isoforms (M) to visualise in silico whether the rs3810950 polymorphism (A120T) can change any features of the tertiary structure of the protein which would have a potential to alter its function. RESULTS: The AA genotype of CHAT was associated with a 1.25 times higher risk of AD (p < 0.002) thus demonstrating that the rs3810950 polymorphism can have a modest but statistically significant effect on the risk of AD in the Czech population. Furthermore, the molecular modelling indicated that the polymorphism is likely to be associated with significant variations in the tertiary structure of the protein molecule which may impact its enzyme activity. CONCLUSIONS: Our findings are consistent with the results of the meta-analytical studies of the relationship between rs3810950 polymorphism and AD and provide further material evidence for a direct (primary) involvement of cholinergic mechanisms in the etiopathogenesis of AD, particularly as a factor in cognitive decline and perturbed conscious awareness commonly observed in patients with AD.
Keywords: Choline O-Acetyltransferase; Polymorphism, Single Nucleotide; Humans; jednonukleotidový polymorfismus; Female; Aged; senioři; lidé; Alzheimer Disease; Genotype; Alzheimerova nemoc; ženské pohlaví; Male; Czech Republic; Aged, 80 and over; senioři nad 80 let; genotyp; Česká republika; mužské pohlaví; cholin-O-acetyltransferasa